(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
The article describes the results of a survey of boxing coaches on the peculiarities of adaptation to training in war conditions and the challenges associated with the requirements of martial law for the training of athletes in general. The results of a survey of female boxers and male boxers on their personal and situational anxiety under martial law are also presented. The survey involved 22 coaches with more than 5 years of work experience and 26 male boxers (aged 17-20 years) and 23 female boxers (aged 17-19 years). It was found that the coaches effectively adapted to the training process under martial law. This can be explained by the peculiarity of the sport, the possibility to continue the training process in a shelter during the air raid alarm, and the use of information and communication technologies for the training process. On the positive side, athletes are self-motivated to train, as this is one of the factors that helps them to cope with stress. This is also related to the age of the athletes interviewed (16-20 years old), as at this age, athletes have a mostly formed psyche. If necessary, coaches increase the frequency of sparring, the number of joint training sessions, and the volume of workload. Coaches also began to cooperate with each other more often to improve the moral climate in teams and optimize sports training, and became more aware of the psychological preparation of athletes. A survey of boxers shows that girls have a higher level of personal and situational anxiety than boys (boys have mostly mild anxiety, girls have medium to low anxiety). This necessitates the search for ways to optimize the educational and training process, paying more attention to the psychological preparation of female boxers during training. At the same time, the results of the study show that coaches and athletes have mostly adapted to martial law and can use the experience gained in further training to level stress.